2017
DOI: 10.1590/2359-3997000000211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on pulmonary function in postmenopausal women following an aquatic exercise program

Abstract: Objective: This study sought to investigate the effects of vitamin D supplementation and aquatic exercise on pulmonary function in postmenopausal women. Materials and methods: This prospective and controlled study included 104 women (62 ± 6.5 years) divided into three groups: a control group lacking vitamin D and calcium supplementation which remained sedentary (CG; n = 17); a control group receiving vitamin D and calcium supplementation which remained sedentary (CDG, n = 33); and a group that completed aquati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…We observed an improvement in the spirometric parameters of women submitted to vitamin D supplementation, even without regular physical exercise. The supplemented group obtained a 7% improvement in peak expiratory flow, similarly forced vital capacity, according to the data presented in Figure 1 [42].…”
Section: Vitamin D Actions On the Respiratory Systemmentioning
confidence: 69%
See 1 more Smart Citation
“…We observed an improvement in the spirometric parameters of women submitted to vitamin D supplementation, even without regular physical exercise. The supplemented group obtained a 7% improvement in peak expiratory flow, similarly forced vital capacity, according to the data presented in Figure 1 [42].…”
Section: Vitamin D Actions On the Respiratory Systemmentioning
confidence: 69%
“…Perhaps in future well-controlled studies, the parameters of cause and effect may be better supported. However, studies have shown that treatment with Vitamin D3 was effective in postmenopausal women to produce a significant increase in plasma concentrations of 25 (OH) D [42]. This adequacy of vitamin D status was associated with improved pulmonary function parameters, independent of the performance of the aquatic exercise program.…”
Section: Resultsmentioning
confidence: 99%
“…What is more, some studies have linked vitamin D actions to restrained proliferation of metalloproteinases of the extracellular matrix (ECM), as well as the regulation of the synthesis to type III collagen by fibroblasts. Thus, the ECM of lung tissue plays an essential role in the pulmonary structures and mechanical properties, thus improving function [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, vitamin D plays a role in regulating human lung fibroblast functions in wound repair and tissue remodeling ( 31 ). In a post hoc analysis, vitamin D supplementation also improved spirometric parameters of lung function in postmenopausal women without regular practice of physical activity, compared with those not supplemented ( 32 ). Additionally, meta-analyses of trials in children, adults, and pregnant women showed that vitamin D supplementation can reduce the risk of exacerbations in patients with mild and moderate asthma who require corticosteroid treatment ( 33 , 34 ).…”
Section: Vitamin D and The Immune Response Against Respiratory Infect...mentioning
confidence: 99%